Systematic Review of the Flabellidae Family (Scleractinia) of the Pirabas Formation (Lower Miocene), Pará State, Brazil - Távora, Vladimir de Araújo; Dias, Jaime Joaquim; Fernandes, Antonio Carlos Sequeira (Anuário do Instituto de Geociências, 2017)
This research deals the systematic review of the corals belonging to the Flabellidae family, assigned to subgenus Flabellum (Flabellum). Were confirmed F. (F.) lyricum Fernandes, 1981 and F. (F.) wailesi Conrad, 1855, as well as the first record of the F. (F.) dens Alcock, 1902 and F. (F.) chipolanum Weisbord, 1971 from the Pirabas Formation. The lithological and preservational settings suggest that these corals lived only in the marine environment and therefore are allochtonnous in the biocalcirudites that occur at B-17 Mine, considered the largest areal extent of the paleolagoon of the Pirabas/Barreiras sequence.